Novel Insights in the Regulatory Mechanisms of Ferroptosis in Hepatocellular Carcinoma - Ma, Shiwen; Adzavon, Yao Mawulikplimi; Wen, Xiaohu; Zhao, Pengxiang; Xie, Fei; Liu, Mengyu; Ma, Xuemei (Frontiers in Cell and Developmental Biology, 2022)
Ferroptosis is a newly defined programmed cell death, which by its mechanism differs from other programmed cell death processes such as apoptosis, necrosis, and autophagy. It has a unique morphology and biological properties that antioxidants and iron-chelating agents can regulate. Ferroptosis has the characteristics of iron ion deposition and dependence on lipid peroxidation. It can affect the progression of many cancers, including liver cancer, by inducing an intracellular iron-dependent accumulation of reactive oxygen species, providing new possibilities for cancer treatment. At present, great progress has been made in exploring the molecular mechanism of ferroptosis. In this review, we summarize the characteristics, mechanisms, and regulatory factors of ferroptosis in detail, discuss the progress of ferroptosis research in liver cancer, and provide directions and new ideas for the treatment of hepatocellular carcinoma.